Midwives and women's perspectives on family planning in Jordan: human rights, gender equity, decision-making and power dynamics - Al-Sheyab, Nihaya A.; Al Nsour, Mohannad; Khader, Yousef S.; Yousif, Hind; Alyahya, Mohammad S.; Taha, Hana; Bardus, Marco; Al Kattan, Malika; Amiri, Mirwais (Heliyon, 2021)
This study explored midwives' and Jordanian and Syrian women's perceptions towards family planning (FP) counseling and the process of FP decision making mechanism to provide evidence for expanding the access and improving the quality and utilization of FP services in Jordan. Explorative qualitative study that purposively recruited 24 women for 4 focus group discussions (FDGs) and 17 midwives for in-depth interviews from two governorates in Jordan. The transcribed narratives were subjected to deductive content analysis. Two themes were extracted from the narratives: The power dynamics in FP decision-making process and the barriers and motivators of FP decision making. The first theme was built on the perceived influence of gender equity and social pressures and gender-based violence on FP decision making. The second theme was constructed on the respondents' beliefs about reproductive health including FP as a human right and their perceptions of the obstacles and facilitators of FP Decision Making. Overall, husbands have an influential role, and perhaps the final say, in deciding whether to use FP services or not as well as the type of method to use. However, wives must initiate the family planning conversation with her husband and do so in a way that will be pleasing to the husband. Whether the husband agrees with the wife's idea to use family planning and gives her permission and funds for use, depends largely on her presentation of the idea, her husband's education level, and his personality. This study revealed several relevant issues that play a role in Jordanian and Syrian women's decision to seek FP services. While cultural and social norms related to family planning and decision making continue to exert pressure on women, women have a deep interest in continuing to broaden their knowledge about family planning services. Engaging men and incorporating digital technology in family planning counselling has the potential to improve shared FP decision-making process among Jordanian couples and overcome some of the barriers. Family planning; Human rights; Gender equity; Power dynamics.